Does mental illness stigma differ across disorders? An investigation of public stigma and attribution theory in social anxiety disorder, depression & schizophrenia - Dabas, Grishma (My University, 2021)
Individuals experiencing mental illness face numerous negative social, economic, and personal outcomes, partly due to the public stigma around mental illness. Attribution theory posits that stigma occurs when publicly held stereotypes of individuals with mental illness elicit negative emotions, eventually resulting in discriminatory behaviours. The stigma associated with common mental disorders is not well understood, especially in the context of attribution theory. The current study aimed to address these gaps through an online survey of undergraduate students’ (n = 302) perceptions of the public’s stigmatizing attitudes, emotions, and behaviours towards an individual depicted as having social anxiety disorder (SAD), depression (DEP) or schizophrenia (SCH). Differences were identified in how strongly specific stigma components were endorsed: SAD and DEP were associated with greater Weak-not-Sick (WNS) attitudes and intentions to help compared to SCH; DEP had the highest blame ratings; SCH had the highest pity ratings; SAD had the lowest avoidance ratings and SCH had the highest. Further, hierarchical multiple regressions revealed that WNS and blame attitudes were a unique predictor of negative affective reactions for SAD and DEP respectively. Dangerousness predicted negative affect for all three disorders. Fear and anger predicted discriminatory behaviours for SAD and DEP, while fear and pity were predictors for SCH. These findings partially supported study hypotheses. Additional exploratory regressions were conducted to identify predictors of pity, help and avoidance. Results from this research suggests that the stigma associated with mental illness is best understood by examining disorder categories individually. Findings can inform the development of effective anti-stigma strategies to improve outcomes for those living with mental illness.
Keywords: Mental illness stigma; Attribution theory; Social anxiety disorder; Depression; Schizophrenia